Development of doppler shift algorithm for modelling sea surface current movements from radar remote sensing data - Marghany, Maged Mahmoud (Faculty of Geoinformation Science and Engineering, 2008)
Ocean surface current requires quick and detailed information, for maps and impact assessment. The ultimate importance of the project relates to development of capacity and manpower in the application of radar remote sensing for coastal zone management plan. This study is solved the Doppler spectra equation by involving two dimensional Fourier transform (2DFFT) to obatin a linear formula of sea radail component. The problem of influnce of bandwidth on imaging moving ocean surface is analytically solved. Based on the maximum peak of Doppler spectra, the horizontal surface current is computed. The Doppler spectra model has been performed in the RADARSAT-1 SAR data. This study concludes that Doppler spectra model is appropriate method to compute sea surface current in the RADARSAT-1 SAR data. The Doppler spectra model has been performed to simulate sea surface current. The maximum sea surface current of 0.7 m/s is observed onshore over water depth of 10 m. The regression model indicated that Doppler spectra model is appropriate algorithm to compute the quantity information of sea surface current.